‘Sarkans Junijs’: Military Relationship between Japan and the Baltic States in the 1930s - Shingo Masunaga (New Zealand, 2022)
This article sheds light on the pre-war military relations between the Baltic States and
Japan throughout 1930s. At first, Hobbesian sense of ‘fears’ against Communism
realized the bilateral and trilateral cooperation in military intelligence sector. The
mutual respects ever since the Russo-Japanese War connected the two distant entities.
Although its main task, toppling the Soviet regimes in Georgia and Ukraine, was
never succeeded, there were some notable achievements and it should be considered
as one of the most successful Japanese intelligence activities in the pre-war period.
However, this fruitful relationship suddenly came to an end by the Soviet invasion of
the Baltic States in June 1940.
APSEC 2016 Conference Proceedings